The Role of Social Support and Academic Resilience on Students' Academic Stress - Basith, Abd; Fitriyadi, Slamat; Suwanto, Insan; Mariana, Dewi; Kamaruddin; Shahinoor Rahman, Md (COUNS-EDU: The International Journal of Counseling and Education, 2025)
Academic stress is one of the impacts of excessive academic pressure on students, so it is necessary to identify various factors that can contribute to the high or low levels of academic stress. Therefore, the objectives of this research are: 1) to describe the levels of social support, academic resilience, and academic stress; 2) to describe the differences in social support, academic resilience, and academic stress based on gender, major, and year of study; 3) to describe the influence of social support and academic resilience on academic stress both directly and indirectly. This research uses a quantitative approach with a cross-sectional study design. The research location is ISBI Singkawang with a population of 650, from which a sample of 248 was taken using the simple random sampling technique. The data collection technique used was measurement with a psychological scale instrument adopted from previous research. The data analysis technique used descriptive statistics, MANOVA, and regression (Hayes Process Macro). The research results show that students' academic stress is in the low category, while social support and academic resilience are in the high category. There are differences in academic stress, social support, and academic resilience based on the major. Then, social support and academic resilience directly influence academic stress, but indirectly result in an insignificant mediating effect. This study has implications for strategies to reduce academic stress, both in individual and institutional contexts.